HUBUNGAN KELENGKAPAN INFORMASI PENUNJANG CT SCAN DENGAN KEAKURATAN KODE DIAGNOSIS CEREBRAL INFARCTION PADA PASIEN BPJS DI RUMAH SAKIT UMUM DAERAH KABUPATEN TEMANGGUNG - UMI KHOLIFAH; ASTRI SRI WARIYANTI; ERNA ADITA KUSUMAWATI (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
One of the factors that affects the accuracy of the Cerebral Infarction diagnosis code is the availability of medical information i.e the supporting result completeness of the CT Scan. The study was aimed at determining the relationship between the completeness of CT Scan supporting information and the accuracy of the Cerebral Infarction diagnosis code for BPJS patients at the Temanggung Regional Public Hospital in 2022. This type of research was analytic observational with a cross-sectional approach. The population were 115 medical record documents and that of 89 were taken as the sample by using simple random sampling. Statistical test used was Chi Square by using SPSS. The results of the study: The characteristic of the patient's age was mostly between 45 to 64 years and that of mostly were female. The length of patients’ treatment was mostly between 4 to 6 days and mostly the discharge patients by the the doctor approval. The completeness of CT Scan results was obtained 71 medical record documents which were complete (79.78%) and that of 18 (20.22%) which were incomplete. Coding accuracy resulted in 64 medical record (71.91%) which were accurate and that of 25 documents (28.09%) which were inaccurate. There was a relationship between the supporting information completeness of CT Scan and the accuracy of the Cerebral Infarction diagnosis code.